Peran Guru Dan Wali Murid Dalam Membina Karakter Disiplin Peserta Didik: ( Studi Kasus Di Salah Satu Sdi Karawang ) - Mar'atussolihah, Fiqhunnisa; Fadhillah Prabowo; Subandriyo (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
In fostering the disciplinary character of students, the roles of teachers and student guardians include: First, the role of the teacher is to be a motivator, facilitator, inspirer, informator and also a guide, the teacher becomes a role model for students in providing good examples in speech or behavior. Second, the role of student guardians such as instilling respect for others, getting children used to obeying the rules that have been agreed upon at home, and ensuring that children do positive activities. While the general methods applied by teachers are, conducting socialization between teachers and student guardians, getting students used to following the rules at school, and being a good role model for students. The special methods applied by the teacher are: giving prizes if students obey school rules well and giving punishment if students violate school rules. The general methods used by student guardians include providing direction and limits in carrying out activities, being a good example for children, educating children to have empathy for others and be responsible for their actions. The specific methods applied by student guardians are making a schedule of children's activities, giving prizes if children reach targets, making agreements together about rules at home and giving punishment if children break the rules at home.